Odpowiedzi

2010-04-15T13:37:23+02:00
Zad8/199
a) 4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8
e) -7 (x-2) = 3x - 1
-7x + 14 = 3x -1
-10x = -15 /: (-10)
x = 1,5
f) 4 (x-1) = 6 (1+x)
4x - 4 = 6 + 6x
-2x = 10 /: (-2)
x = -5
zad9/199
a) 0,2x + 0,3 = -0,5
0,2x = -0,5 - 0,3
0,2x = -0,8 /: (0,2)
x = -4
d) -1,5x - 3 = 0,2x + 6
-1,7x = 9 /: (-1,7)
x = 5,29 (około)
3 3 3
2010-04-15T13:41:50+02:00
A] 4x - 3= 3x + 5
4x - 3x= 5+3
x=8
e]-7 [x-2] = 3x - 1
-7x+14 = 3x-1
-7x-3x=-1-14
-10x= -15 / :(-10)
x=1,5

f] 4 [x-1] = 6 [1+x]
4x-4 = 6+6x
4x-6x= 6+4
-2x=10 / :(-2)
x= -5

a] 0,2x + 0,3= -0,5
0,2x=-0,5 - 0,3
0,2x = -0,8 / 0,2
x = -4

d] -1,5x - 3=0,2x +6
-1,5x - 0,2x = 6+3
-1,7x=9 / (-1,7)
x=-5,3
3 3 3
2010-04-15T13:45:26+02:00
Zad 8
a] 4x - 3= 3x + 5
4x-3x-3=5 /+3
4x-3x= 5+3
x=8

e]-7 [x-2] = 3x - 1
-7x+7=3x-1 /+1
-7x+8=3x /+7x
8=10x /: 10
x=0,8

f] 4 [x-1] = 6 [1+x]
4x-4=6=6+6x/ -4x
-4=6+2x /-6
-10 = 2x /:2
-5=x

Zad 9

a] 0,2x + 0,3= -0,5 / - 0,3
0,2x= -0,8 / : 0,2
x = - 4




3 3 3